THE EFFECT OF READING AL – QURAN ON MENTAL HEALTH - Fairuz Rizka Ghazalah (Psikoeduko: Jurnal Psikologi Edukasi dan Konseling, 2021)
This article discusses how much influence reading the Koran has on the mental health of an individual, that when an individual reads the Qur'an many psychological effects occur in his body that affects mental health. The writing of this article was assisted by research conducted using literature studies. As for the background of this writing is the rise of mental health cases in Indonesia today and occurs in all groups, ranging from children, adolescents, and adults, especially in millennial adolescence. Also, the background of this article is written on the background of one of the verses of the Koran in Surah Fussilat verse 44 which means "The Koran is a guide and an antidote for believers, and for those who do not believe in them, there is a blockage in their ears. them ”, that the Koran is a remedy for all diseases, whether physical or mental.